2020
DOI: 10.3390/ijms21072358
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chondrocyte Hypertrophy and Senescence in Osteoarthritis Initiation and Progression

Abstract: Osteoarthritis (OA) is the most common joint disease that causes pain and disability in the adult population. OA is primarily caused by trauma induced by an external force or by age-related cartilage damage. Chondrocyte hypertrophy or chondrocyte senescence is thought to play a role in the initiation and progression of OA. Although chondrocyte hypertrophy and cell death are both crucial steps during the natural process of endochondral bone formation, the abnormal activation of these two processes after injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(173 citation statements)
references
References 105 publications
3
141
0
Order By: Relevance
“…The matrix that encapsulates chondrocytes plays a role of lubrication and mechanical support for cartilage joint. Although chondrocytes account for only 1% of the total cartilage volume, it plays an indelible role in maintaining the integrity of the matrix (Charlier et al, 2019;Rim et al, 2020). In fact, when certain factors act on the cartilage matrix and change its structure, chondrocytes can respond accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix that encapsulates chondrocytes plays a role of lubrication and mechanical support for cartilage joint. Although chondrocytes account for only 1% of the total cartilage volume, it plays an indelible role in maintaining the integrity of the matrix (Charlier et al, 2019;Rim et al, 2020). In fact, when certain factors act on the cartilage matrix and change its structure, chondrocytes can respond accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of OA is still indeterminate. Chondrocyte hypertrophy, senescence, and apoptosis are regarded as crucial biological events during the initiation and development of OA ( Charlier et al, 2016 ; Rim et al, 2020 ). In the present work, it was demonstrated that the MEG3/miR-9-5p/KLF4 axis was involved in regulating the viability, migration, apoptosis, and inflammatory response of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the cartilage environment ultimately reset the chondrocyte cell cycle and lead to abnormal chondrocyte proliferation and hypertrophic differentiation, which eventually results in chondrocyte apoptosis [ 50 , 51 ]. While the hypertrophic differentiation of chondrocytes is a normal pathway in developmental events, abnormal hypertrophic differentiation in adult cartilage is one of the causes of OA [ 54 ].…”
Section: Fibrosis and Oamentioning
confidence: 99%